Opportunities to Achieve a Sustainable Restaurant Business - Olga Mancheva-Ali; Iliyan Lilov (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
This report examines the place of restaurant business in the tourism system and its importance in the formation and realization of the tourist product. Due to its leading role in tourism, opportunities are being sought to apply new tools and methods to achieve sustainable development, including reducing its harmful impact on the environment and creating new, more favourable habits for consumers. There is a study of good practices in the world and their potential application in Bulgarian catering establishments as possible ways to achieve sustainable restaurants. In addition, a survey is conducted among potential users of restaurant services to determine their attitude and role in achieving sustainable results.
Keywords: Z32; 330; sustainability; restaurant business; development